„Ritualistic” priests and landowners’ funerals in the Minsk guberniya in the second half of the 19th century. Announcement - Jurkowski, Roman (Requiem, 2025)
The article is information about research problem describing the relationship between Polish landowners from the Minsk Governorate and Catholic priests, called „ritualists” who adopted the Russian language in the so-called additional services. The situation took place in the second half of the 19th century, after the January Uprising, when, under pressure from the Russian authorities and despite the Vatican, some Catholic priests used the Russian language during Catholic masses and during funerals. This caused strong resistance from the Polish Catholic landed gentry, who did not want to hear the Russian language during such sad celebrations as family funerals. The article presents three funerals in the well-known borderland Wańkowicz family, during which the mourners were forced to accept the presence of a „ritualist” priest.